Colonic disease recurrence following proctectomy with end colostomy for anorectal Crohn's disease. (12th July 2021) - Lightner, Amy L.; Steele, Scott R.; Delaney, Conor P.; Lavryk, Olga; Vaidya, Prashansha; McMichael, John; Jia, Xue; de Buck van Overstraeten, Anthony; Brar, Mantaj S.
Abstract: Aim: In patients with anorectal Crohn's disease, it remains uncertain whether a total proctocolectomy with end ileostomy or proctectomy with end colostomy should be recommended due to the unknown rate of disease recurrence in the remaining colon. Methods: A retrospective review of all patients with a known diagnosis of Crohn's disease who underwent a proctectomy with end colostomy for distal Crohn's disease between January 1, 2010 and January 1, 2019 at two IBD referral centres was conducted. Data collected included patient demographics, surgical variables at the time of proctectomy, and postoperative clinical, endoscopic and surgical recurrence rates. Results: A total of 63 patients were included; mean age was 47 years (SD 15 years) and 32 (50.8%) were female. The majority of patients underwent a proctectomy with end colostomy ( n = 56; 88.9%) while the remaining seven patients (11.1%) underwent a proctectomy with end colostomy and concurrent ileocectomy. A total of 55 patients (87.3%) had proctitis, 51 (81%) had perianal fistulating disease, and 34 (54%) had anal canal stenosis or ulceration. Most patients had medically refractory disease ( n = 54; 85.7%) versus neoplasia ( n = 9; 14.3%). The median length of long‐term follow‐up was 17.7 months (IQR: 4.72, 38.7 months). During that time, 14 (22.2%) experienced clinical recurrence, 10 of 34 evaluated (29.4%) had endoscopic recurrence, and 3 (4.76%) required a completion total abdominal colectomy for recurrent medically refractory disease in the colon. Conclusion: Colonic recurrence remains low following proctectomy and descending colostomy suggesting this operative management strategy is reasonable in Crohn's patients with distal disease.